Past and present diploma in forestry program in Malaysia - Ong, Kian Huat; John, Keen Chubo; King, Jie Hung (2010)
In Malaysia, forester roles are changing, shifting towards social and environmental conservation from traditional forestry. In order to meet such changes, emphasis are made on personal, social, interdisciplinary and problem-solving skills to help forester in dealing with human aspects of forestry and managing as well as applying multidisciplinary and participatory approaches. This paper highlights on the latest approach by Universiti Putra Malaysia in reviewing and developing a new curricula for its Diploma in Forestry Program. It traces the development of diploma program in Malaysia, its past and future direction. Discussion on changing requirements in the forestry profession especially semi-professional forester will also be discussed.